Pemanfaatan Limbah Serbuk Bata Merah Sebagai Bahan Stabilisasi Tanah Lempung Ekspansif - Rama Indera Kusuma; Enden Mina; Woelandari Fathonah; Zera Ilham Yasin (Jurnal Ilmiah Rekayasa Sipil, 2022)
The swell-shrink behavior of expansive clay soil cause problems in the construction such as the occurrence of bumpy road, cracking and various other problems, therefore stabilization of the soil is needed to improve the behavior of the soil.Red brick is a building material that contains chemical compounds that can increase the compressive strength of a building. Red brick waste which is rarely used is then reused as a cement mixture.This study aims to determine the type and classification of soil in Cibingbin village, a village located in Cibaliung sub-district, Pandeglang district-Banten province, based on the USCS soil classification system, and to determine the value of unconfined compression test (qu) with the addition of red brick powder with variations the percentage additions were 0%, 5%, 10%, and 15% with curing times of 0, 7, 14, and 28 days.From the results of the study, it was found that the soil classification in Cibingbin village was classified as high plasticity organic clay (OH) according to the USCS classification system. The lowest qu value was obtained at 0 days of curing with the percentage of added ingredients 0%, 5%, 10%, 15% increasing the qu value was 1,316 kg/cm2, 1,655 kg/cm2, 2,242 kg/cm2; 2,607 kg/cm2, and the largest qu value was obtained at 14 days of curing with the percentage of added material 0%, 5%. , 10%, 15% obtained 1,639 kg/cm2, 3,189 kg/cm2, 3,440 kg/cm2, dan 3,603 kg/cm2. Keywords: Stabilization, Unconfined Compression Strength, Waste Red Brick